Fabrication of Automatic Green Board Cleaner - Harshal Bramhankar; Vaibhav Thawari; Mahesh Marathe; Prathamesh Chintawar; Dinesh Burkunde; Aryan Wankhade (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Maintaining cleanliness on classroom green boards is essential for effective learning and a dust-free environment. Traditional manual cleaning methods are time-consuming, inconsistent, and result in chalk dust dispersion, which can cause respiratory issues for users. To address these challenges, this project presents an Automatic Green Board Cleaner, a mechanized system designed to clean green boards efficiently and uniformly with minimal human intervention. The proposed system consists of a motor-driven mechanism with a reciprocating duster mounted on a linear guide rail. The duster moves horizontally across the board, removing chalk dust effectively. Key components include a belt and pulley system, linear motor holder, reciprocating guide plate, rail bracket, and a power supply unit. The device operates via an electrical switch, ensuring ease of use. The system was tested under various conditions to evaluate its cleaning efficiency, operational speed, and durability. Results indicate that the automatic cleaner provides a more consistent and time-saving cleaning process compared to manual methods. The design is cost-effective, energy-efficient, and can be integrated into modern classrooms to enhance convenience. This project contributes to the development of smart classroom technology, and future improvements could include automated activation, dust collection mechanisms, and integration with IoT for remote control.